The Acehnese Loanwords and Contact with Other World's Languages: A Preliminary Findings - Akmal, Saiful; Harley, Lala Barzanzia; Rahmikawati, Rahmikawati; Maulida, Titin Arifa (Lingua Cultura, 2022)
The research aimed to uncover some Acehnese loanwords’ etymological and historical roots, which may help unravel the relationships between the world’s languages. The method applied in the research was the word-etymology model or lexical etymology to trace the word’s origins in historical linguistics. In addition, the systematic comparison with other related languages and semantic change typology were also exercised for the purpose of analysis. The data consisted of some selected Acehnese loanwords from the phone interviews with the participants selected purposively in different districts in Aceh. The findings reveal that the Acehnese language is etymologically categorized as part of the Austronesian language (Chamic and Malay), Arabic Afro-Asiatic language, Sanskrit (Bengali, Urdu, Gujarat), English, and Indo-European. The research attests that Acehnese loanwords may also be influenced by cross-language loanwords and borrowings simultaneously, such as Arabic from the Afro-Asiatic language family, Dutch or German, and English from the Indo-European language.